The United Nations in Bangladesh - Oliver, Thomas W. (Princeton : Princeton University Press, 1978)
This book provides the first analytic account of the United Nations relief operation in Bangladesh. Written by a United Nations staff member involved in the operation, it reflects his direct access to archives and thus offers a doubly valuable description of the inner workings of an international organization. The unusually large relief program in Bangladesh has been described as ""a rare example of international cooperation that has enlarged the scope of constructive United Nations action."" Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technolo.
*Frontmatter, pg. i*Contents, pg. v*Foreword, pg. vii*Acknowledgments, pg. ix*List of Abbreviations, pg. xi*Map of Transportation Network of Bangladesh, pg. xii*Introduction, pg. xiii*CHAPTER 1. The Secretary-General's Offer of Assistance: March-June 1971, pg. 1*CHAPTER 2. UNEPRO-The Start-Up: June-July 1971, pg. 16*CHAPTER 3. The Wider Issues: July-August 1971, pg. 32*CHAPTER 4. The Operation Takes Shape: August-November 1971, pg. 43*CHAPTER 5. The Secretary-General's Offer of Good Offices: October-November 1971, pg. 61*CHAPTER 6. UNEPRO-The Attempted Evacuation: December 1971, pg. 72*CHAPTER 7. The End of UNEPRO: December 1971, pg. 80*CHAPTER 8. UNROD-The Early Days: December 1971 - February 1972, pg. 98*CHAPTER 9. UNROD-The End of the Beginning: March-April 1972, pg. 113*CHAPTER 10. The Consolidation of the Operation, pg. 130*CHAPTER 11. The Right Road: May-September 1972, pg. 142*CHAPTER 12. UNROD-The Last Six Months: October 1972-March 1973, pg. 155*CHAPTER 13. Winding Up the Operation: April-December 1973, pg. 168*CHAPTER 14. How the Operation Worked, pg. 183*APPENDIX 1. UNEPRO, UNROD, UNROB: A Chronology, pg. 203*APPENDIX 2. Published United Nations Material, pg. 207*Notes, pg. 211*Index, pg. 227
Includes bibliographical references and Index
SOL
Trim Education
Keywords: United Nations -- Bangladesh; International relief -- Bangladesh; Law